Talent Management Strategies and Employee Productivity in Information Technology Sector - Dr. P. S. Nagarajan, U. Devika (International Journal of Advanced Science and Technology, 2019)
Contemporaryorganizations accept Talent Management as a business strategy that would enable to retain talented employees to improve organizations’ productivity. The radical and essential part; is identifying the talents, hone and enable them to improve their performance which leads to high productivity. The major objective of this research work is to understand the talent management strategies and its impact on employee productivity. The present study has been mainly based on survey method. Primary data have been collected through questionnaires which was prepared and administered to the IT sector employees at all levels.Keyword:. Talent Management Talent management strategies Employee productivity